Urban Forest Educational Resources for Teaching Youth - Jennifer Seitz; Martha Monroe; Francisco Escobedo (EDIS)
FOR-172, a 5-page fact sheet by Jennifer Seitz, Martha Monroe, and Francisco Escobedo, lists and describes resources available to assist educators, extension agents, home school parents, foresters, and nature center staff as they help youth become more aware of the urban forests in their backyard. Published by the UF School of Forest Resources and Conservation, January 2008.